Association of IL-1B rs16944 Polymorphism With Acute Encephalopathy With Biphasic Seizures and Late Reduced Diffusion Is Opposite to That of Febrile Seizures - Shibata, Akiko; Kasai, Mariko; Hoshino, Ai; Mizuguchi, Masashi (Frontiers in Neurology, 2022)
Objective Acute encephalopathy with biphasic seizures and late reduced diffusion (AESD) is a severe neurologic complication of febrile infectious diseases in children. At the onset, AESD is clinically manifested as febrile status epilepticus. Subsequent damage to the cerebral cortex is ascribed to neurotoxicity. The incidence of AESD is remarkably high in Japan, suggesting the involvement of genetic factors. The expression of interleukin 1 beta (IL-1β), a member of the cytokine family involved in the inflammatory response, is reportedly associated with rs16944, a polymorphism in the upstream region of the IL-1B gene, being higher in TT genotype. Previous association studies of rs16944 with febrile seizures (FS) have demonstrated a significant excess in the TT vs. CC + CT genotype in the Asian population. Here, we conducted a case-control association study of rs16944 in AESD. Methods We genotyped rs16944 by Sanger sequencing on 283 patients with AESD. As controls, we used genotyping data of 104 Japanese individuals obtained from the 1,000 Genomes Project. Then, we performed a case-control association study using the chi-square test. Results The ratio of individuals with TT vs. those with CC+CT genotype was significantly lower in AESD than in the controls [p-value 0.021, Odds Ratio (OR) 0.52]. This finding was opposite to that of a previously reported FS. Conclusion The AESD has a genetic background distinct from FS and is not a severe type of FS.